Landslide and landslide-talus processes on the roads of the Рrigorodny district and the urban district of Vladikavkaz (the Republic of North Ossetia – Alania) - V. V. Razumov; N. D. Bogdanova; N. V. Razumova; N. V. Kondratyeva; V. A. Shalnev (Наука. Инновации. Технологии)
The object of the study is landslide, rockfall and talus activity on the highways of the Prigorodny administrative district and the urban district of Vladikavkaz in the Republic of North Ossetia – Alania. The paper classifies and analyzes various sources containing information on the conditions and causes of the development of landslide and talus processes, as well as the activity and danger of their manifestation on the roads of these municipalities over 2002–2023. The activity of the studied processes is mainly due to man-made effects and the influence of natural rapidly changing factors (meltwater, precipitation and air temperature). Landslides and active rockfall and talus areas threatening highways in the studied municipalities have been identified. Over the studied period, about 10 significant landslides (with material damage) and more than 40 rockfall and talus occasions took place on these roads. The maximum number of cases is confined to the spring and summer period. The study provides information on the scale of landslide, rockfall and talus deformations and destructions of the roadbed that have occurred. The areas where manifestations of the studied processes were periodically observed in different years are specified. The activity of landslide movements over the studied period was insignificant, its volume, in general, did not exceed 20.0 thousand m3. The area of talus deposits varied from 3.0 to 60.0 thousand m2, and the volume of rockfall was in most cases 250–500 m3. Large accumulations of loose material were observed on roads in the valley of the Gizeldon River, and rockfall mainly occurred on the Georgian Military Road (the Balta – Upper Lars section). The maximum length of sections of republic highways affected exposed to rockfall and talus processes was noted in 2017, and to landslides – in 2022. The analysis of socio-economic consequences of the intensification of the studied processes on the roads of the Prigorodny district and the urban district of Vladikavkaz allows the authors to conclude that the landslide threat to the road infrastructure of these municipalities is low and the rockfall and talus threat is rather significant.